Inequality stability. Chile 1990-2003 - Larrañaga, Osvaldo; Valenzuela, Juan Pablo (Estudios de Economía, 2016)
This study measures the impact of changes in the income determinants on inequality in the 1990 to 2003 period, in order to answer the question of why income distribution as a whole has not changed. The methodology utilized are micro-simulations of income distribution, which is the most appropriate technique for analyzing the relationship between changes in determinant factors and changes in income inequality. It is analyzed the role of returns, participation rates, occupational choices, schooling endowments, subsidies, pensions and household size. The inertia shown by inequality reflects the interplay of factors that cancel each other out, others that operate slowly over time, and the emergence of new developments that affect distribution. Furthermore, there are no clear indications that this situation will change over the next few years. Progress in this area will require a more active public policy than in the past.